Monitoring the Tectonic Plate Movements in Turkey Based on the National Continuous GNSS Network - Uzel, Turgut; Eren, Kamil; Gülal, Vahap Engin; Tiryakioğlu, İbrahim; Dindar, Ahmet Anıl; Yılmaz, Haluk (Springer Heidelberg, Tiergartenstrasse 17, D-69121 Heidelberg, Germany, 2013)
In recent decades, the space geodesy has been applied to the areas such as transportation, infrastructure planning, navigation, etc. Among them, the precise positioning at the Global Navigation Satellite System (GNSS) stations yields better view in the understanding of the crustal deformation that requires global-scale measurements. There have been numerous studies examining the data process of continuous GNSS observations in the field of earth monitoring. More recently, GNSS stations established for continuously operating reference station networks have been beneficial resources in the tectonic plate-monitoring studies in lieu of campaign-type observations. However, this requires that the Continuously Operating Reference Station (CORS) should be established on stable structures acting like foundations and requires investigation of the long-term repeatability time series. This study aims to introduce recently established national CORS network, named CORS-TR, covering the entire Turkey and Northern Cyprus, and to explain the process of the long-term data obtained from the network on the characteristics of the tectonic plate movement within the area. The results of the CORS-TR data process present a great potential of using continuously operating reference stations not only in real-time kinematic applications of conventional geodesy studies but also in detecting and monitoring the crustal deformations of those that are crucial in earthquake-prone areas like Turkey. Since the findings are computed from the results of the all permanent stations of CORS-TR network, this study also examines the GNSS observation quality of the network for the given time interval. One of the major conclusions of the data process conducted in the study displays that the CORS-TR stations established on the carefully selected large and low-rise existing building had been more stable than the stations on the ground which have been subjected to soil settlement since the construction.
Keywords: plate tectonic; GNSS; CORS network; system; evolution; dynamics; sistem; evrim; dinamik; levha tektoniği